Factors of Emigration from Russia: Regional Features - Khramova, Marina Nikolaevna; Ryazantsev, Sergey Vasilyevich (Economy of Regions, 2018)
The research of the factors of emigration from Russia taking into account regional features is a relevant topic for modern Russia. Despite essential emigration decrease of Russians, in comparison with the 1990th, a problem remains critical. Along with general tendencies, in the regions of Russia, a wide range of factors determining the scales and directions of emigration from Russia has emerged. The identification of a role and quantitative assessment of the effect of these factors will promote the creation of more effective mechanisms for the modern migration policy of the Russian Federation. We consider the scale, dynamics and specific features of the emigration of Russians in the post-Soviet period. The paper indicates the shortcomings of statistical accounting of emigrants from the Russian Federation. Several waves of emigration have been singled out, which differ significantly in their qualitative and quantitative characteristics. Based on the analysis of the constructed indicators characterizing the emigration activity of Russians, we have revealed the peculiarities of emigration in the regions of Russia. We used the regression analysis to quantify the factors responsible for the emigration activity of the population. As initial information for the analysis, we used the official data of Federal State Statistics Service on the number of the Russian citizens who have gone abroad for 2014 considering a region as well as a number of the socio-economic indexes characterizing the level and quality of life of the population. Russians from the border regions are more likely to travel to a permanent place of residence abroad than residents of other regions of the Russian Federation. In the course of time, there was a significant expansion of the directions and channels of emigration, and the socio-demographic portrait of the emigrant has also changed. Emigration from Russia has become “younger”. To a greater extent, women are involved in emigration mainly through the marriage channel. The emigration activity of Russians is significantly influenced by several factors in the regions of current residence. Among these factors, indicators that characterize tensions in regional labour markets and those that play the role of “pushing out” are particularly noted. At the same time, the restraining factor is the proportion of the population with incomes below the subsistence level. The paper also analyses the socio-demographic and economic consequences of emigration. The results of the study can be used to improve the migration policy of the Russian Federation.